2019
DOI: 10.1111/apa.14788
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study showed that a culturally tailored parenting programme improved the confidence and skills of Somali immigrants

Abstract: Aim Parenting programmes tailored to immigrant parents have been reported to improve the mental health of the children and parents, as well as parents’ sense of competence in parenting. However, research on parents’ experiences of programmes tailored to their needs is scarce. This qualitative study aimed to describe Somali parents’ experiences of how a culturally sensitive programme affected their parenting. Methods The study was conducted in a middle‐sized city in Sweden in 2015. Data were collected through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…In addition, there are a few vulnerable areas with a relatively high crime rate in which the majority of the Somali population lives. The research was part of a long-term follow-up study in which Somali-born parents involved in a culturally tailored parenting support programme were interviewed (Osman et al, 2019(Osman et al, , 2017(Osman et al, , 2016. In this study, we aimed to understand their children's perspectives on their acculturation and what support they needed.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…In addition, there are a few vulnerable areas with a relatively high crime rate in which the majority of the Somali population lives. The research was part of a long-term follow-up study in which Somali-born parents involved in a culturally tailored parenting support programme were interviewed (Osman et al, 2019(Osman et al, , 2017(Osman et al, , 2016. In this study, we aimed to understand their children's perspectives on their acculturation and what support they needed.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Our findings showed that the Ladnaan Programme decreased children's behaviour problems [15] and improved parents' mental health and sense of parental competence [16]. Somali-born parents reported that the culturally tailored parenting programme strengthened their parenting and parent-child relationship [26]. Because of the proven benefits of the programme, it is crucial to explore how the implementation of the programme and its reach to the target group were obtained in order to guide future implementation of similar programmes and to provide information to policymakers about the potential of the programme to be employed in other settings.…”
Section: Introductionmentioning
confidence: 60%
“…Our ndings showed that the Ladnaan Programme decreased children's behaviour problems [15] and improved parents' mental health and sense of parental competence [16]. Somali-born parents reported that the culturally tailored parenting programme strengthened their parenting and parent-child relationship [26]. Because of the proven bene ts of the programme, it is crucial to explore how the implementation of the programme and its reach to the target group were obtained in order to guide future implementation of similar programmes and to provide information to policymakers about the potential of the programme to be employed in other settings.…”
Section: Introductionmentioning
confidence: 68%